Trends in female applicants to Canadian ophthalmology residency programs from 1998-2020 - McDonald, Heather M; Cote, Stephanie L; McMillan, Austin; Sharan, Sapna (Canadian Medical Education Journal, 2024)
Background: Ophthalmology has historically been a male-dominated specialty. Despite there being a higher proportion of females in Canadian medical schools since the early 2000s, it is unknown if trends in female applicants and those accepted to ophthalmology have followed suit. This study aims to evaluate trends in gender representation of ophthalmology applicants to Canadian residency programs from 1998 to 2020 and to compare those trends to other surgical specialties. Methods: We obtained aggregate data of the annual number of male and female applicants ranking and successfully matching to ophthalmology as their first-choice specialty from the Canadian Residency Matching Service (CaRMS) database. We then carried out a retrospective cross-sectional analysis on the publicly available data. Subsequently, we compared trends in female applicants to ophthalmology, as well as female practicing ophthalmologists, to other surgical disciplines. Results: The proportion of female applicants increased from 24.3% in 1998 to 33.3% in 2020 (p = 0.001), and matched female applicants increased from 28.6% in 1998 to 40.5% in 2020 (p = 0.023). However, the incremental change in proportion did not statistically significantly increase in 2008-2012, 2013-2016, and 2017-2020. Comparison of male and female matching success rates did not reveal a significant difference (p = 0.45). Trends in female applicants to ophthalmology and female practicing ophthalmologists were similar to other surgical specialties. Conclusions: Although the proportion of female applicants is increasing, there is a recent plateau and an inability to equalize the female-to-male ratio in ophthalmology. Further studies are needed to identify potential barriers and mitigate possible residual gender biases.